MENEJEMEN INOVASI STRATEGIS DANADOPSI DIGITAL MARKETING UPAYA MEMBANGUN KEUNGGULAN BERSAING DAN KINERJA BISNIS IKM TENUN TROSO KABUPATEN JEPARA - Endang Swastuti (STIE Pelita Nusantara Semarang, 2020)
The purpose of this research is to investigate the impact of management innovation and adoption of digital marketing strategies in relation to competitive advantage and performance. The object of this study is the IKM Troso Weaving Troso of Jepara Regency with an observation unit of 169 respondents consisting of managers and heads of marketing. Data were analyzed with structural equation model (SEM) to test the research hypothesis. The analysis revealed that the innovation strategy and adoption of digital marketing significantly increased the competence and performance of the company. The implication of this finding is that companies need to pay attention to the values of corporate culture such as determining the direction of business development, increasing productivity and creativity, developing the quality of goods and services and motivating employees to achieve the highest achievements. While managerial implications related to organizational readiness include making a budget for information technology updates on a regular basis, making it easier for employees to make improvements to marketing information technology